Learning to Understand Others Through Relationally Oriented Reading. (2nd May 2013) - Lysaker, Judith; Tonge, Clare
Abstract Children with reading difficulties often face social and emotional challenges as well. These struggles may be particularly taxing for these children as classrooms increase in diversity and they encounter fewer people like themselves. In response to these issues, we developed an approach to teaching reading called Relationally Oriented Reading Instruction (RORI) which attempts to build relational capacities through a systematic approach to reading picture books. In this article we present the background and rationale for this approach, describe its implementation, as well as what we learned from that implementation.